Optimalisasi Pencegahan Kanker Serviks melalui Promosi Kesehatan Reproduksi pada Kelompok Wanita Usia Subur - Wahyu Nuraisya; Nunik Ike Yunia Sari (Poltekkes Kemenkes Kendari, 2022)
Cervical cancer is a type of cancer with a large prevalence. Health promotion is one of the primary prevention efforts that can be done to prevent death from cervical cancer. This reproductive health promotion activity is carried out using the lecture method, showing videos and pictures, and questions and answers which begin with the pre-test and end with the post-test. Health promotion material, namely cervical cancer. This activity was carried out at the Darungan Village Hall, Pare District, Kediri Regency on May 12, 20 and 21 2022. The target of the activity was 30 women of childbearing age. The results obtained from this reproductive health promotion are increased knowledge of women of childbearing age about reproductive health problems and early detection of cervical cancer, from the sufficient category of 56.6% to the good category of 86.6%. Reproductive health promotion needs to be given to women of childbearing age to increase knowledge and awareness about cervical cancer prevention.